Buddhist economics: a model for managing consumer society. Issue 8 (2nd September 2014) - Mutakalin, Gullinee
Abstract : Purpose: – The purpose of this paper is to critically evaluate consumer society through various perspectives. In addition, it applies Buddhist economics as an exemplary model which helps managing consumer society. Design/methodology/approach: – The study started by comparing and contrasting the management of consumption between Mainstream and Buddhist economic. In addition, various perspectives such as Marxian economics, Frankfurt School, sociology as well as social critics are added to comprehend consumer society. Finally, it proposed the practices of Buddhist economics as an exemplary model for managing consumer society. Findings: – The study found that while Mainstream economics focusses on increasing the amount of goods and services, Buddhist economics focusses on converting the insatiable to satiable desires. There are two viewpoints of the interconnected spheres of consumption and production through the evolution of consumerism; a producer-led approach and a consumer-led approach. This polarization presents the debate in a very well-established tension between structure and agency. Originality/value: – This paper proposed an exemplary model for managing consumer society by applying the dialectical relationship of both structure and agency.